2012
DOI: 10.1016/j.jamda.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The Bridge Project: Improving Heart Failure Care in Skilled Nursing Facilities

Abstract: Introduction Re-hospitalization rates and transitions of care for patients with heart failure (HF) continue to be of prominent importance for hospital systems around the United States. Skilled nursing facilities (SNF) are pivotal sites for transition especially for older adults. The purpose of this study was to evaluate in SNFs both the 1) current state of HF management (HF admissions, protocols and staff knowledge) and 2) the acceptability and effect of a HF staff educational program Methods Four SNFs parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…A small number of non-randomized studies evaluating HF management interventions in LTC suggest that such initiatives can reduce health service utilization [14][15][16][17][18][19]. However, these interventions relied on access to substantial resources beyond those normally available in LTC homes and targeted less frail residents expected to return to the community.…”
mentioning
confidence: 99%
“…A small number of non-randomized studies evaluating HF management interventions in LTC suggest that such initiatives can reduce health service utilization [14][15][16][17][18][19]. However, these interventions relied on access to substantial resources beyond those normally available in LTC homes and targeted less frail residents expected to return to the community.…”
mentioning
confidence: 99%
“…Social and environmental factors may influence the severity and adaptability of aging process in older HF patients. Advanced age has been implicated as predictor of re-admissions [20][21][22]. In 161 elderly patients that had four or more HF admissions, it was found that one of the predictors of readmission was increasing age [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Education for staff, patients, and families is the second component of the SHU model, as it has been shown to impact health outcomes for SNF HF patients (Boxer et al, 2012). Curricula for the education of the SHU staff were adapted from the Bridge Program, an ongoing initiative in a Midwestern university hospital system, that has produced evidence of improvement in HF-related knowledge among the staff (Boxer et al, 2012).…”
Section: Skilled Heart Unit Model Of Carementioning
confidence: 99%
“…Curricula for the education of the SHU staff were adapted from the Bridge Program, an ongoing initiative in a Midwestern university hospital system, that has produced evidence of improvement in HF-related knowledge among the staff (Boxer et al, 2012). Educational resources put forth by the Heart Failure Society of America and the American Heart Association were used for patient/family education program (Lindenfeld et al, 2010).…”
Section: Skilled Heart Unit Model Of Carementioning
confidence: 99%